Perceived ease of use, usefulness, and task interdependence: impacts on employee performance in higher education - Inayati Mandayuni; Kiagus Muhammad Sobri; Alfitri Alfitri; Andries Lionardo (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2025)
This research aimed to investigate the relationship between perceived ease of use (PEU), perceived usefulness (PU), and task interdependence (TASKINT) on employees’ work performance. Technology acceptance model (TAM) was used as a theoretical perspective to explore technology adoption in the context of employees in higher education using electronic asset management (EAM). Moreover, a quantitative method was used to explain the causality of the relationship between the variables, and a total of 380 respondents were determined as the sample. The results showed that PEU and usefulness had a significant effect on TASKINT. Even though PEU and TASKINT had a significant effect on employees’ work performance, PU did not have a significant effect. In addition, the results showed TASKINT significantly mediated the relationship between perceived ease of use, usefulness, and employees’ work performance. These findings imply that enhancing the ease of use and fostering TASKINT can lead to improved employee performance when adopting new technologies. For higher education institutions (HEI), focusing on user-friendly systems and promoting collaborative tasks can maximize the benefits of technology implementation on work performance.